Vitamin D Deficiency and Metabolic Sindroms: Literature Review - Yuli Indarti (Universitas STRADA Indonesia, 2021)
Based on current research, lack of micronutrients, especially Vitamin D, is thought to be associated with metabolic disorders. A good understanding of vitamin D deficiency as a risk factor for metabolic disorders is the basis for establishing policies and programs. This study aimed to determine the relationship between vitamin D and metabolic syndrome (MetS) and its parameters. Search for articles in literature review through Scientdirect, PubMed, Medline, and Google Scholar were publication periods between 2010-2019. Vitamin D/serum 25 (OH) D levels is associated with obesity, hypertention, glycemia index but studies relating vitamin D deficiency and lipid profiles have not shown consistent results. Most of research found association of Vitamin D and Metabolic Syndrome (MetS). Based on the review, most of the study results indicate that Vitamin D is associated with parameters in the metabolic syndrome, so that Vitamin D could be a new risk factor for MetS